The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1039/d1dt01482j
|View full text |Cite
|
Sign up to set email alerts
|

A review on metal–organic framework-derived anode materials for potassium-ion batteries

Abstract: In recent years, metal-organic frameworks (MOFs) have been widely used in various fields, including electrochemical energy storage and conversion because of their excellent properties, such as high specific surface area,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…[264][265][266][267][268] The conductive carbon (eg, graphene, carbon nanofibers/nanotubes) have shown a great promise as the 3D host materials in recent alkali-metal batteries. 260,[269][270][271][272][273][274][275][276][277][278][279][280] Li et al 270 reported 3D porous carbon network promoted a uniform distribution of current density resulting in carbon network mitigating the formation of Li dendrite effectively. Wu et al 275 suggested rGO aerogel as stable host for NIB, which reveals excellent cycling stability at a high current density of 5 mA cm À2 .…”
Section: Carbon Host For Metal-free Anodementioning
confidence: 99%
See 1 more Smart Citation
“…[264][265][266][267][268] The conductive carbon (eg, graphene, carbon nanofibers/nanotubes) have shown a great promise as the 3D host materials in recent alkali-metal batteries. 260,[269][270][271][272][273][274][275][276][277][278][279][280] Li et al 270 reported 3D porous carbon network promoted a uniform distribution of current density resulting in carbon network mitigating the formation of Li dendrite effectively. Wu et al 275 suggested rGO aerogel as stable host for NIB, which reveals excellent cycling stability at a high current density of 5 mA cm À2 .…”
Section: Carbon Host For Metal-free Anodementioning
confidence: 99%
“…Analogous to LIB and NIB systems, the carbon materials for the host have been applied to KIB. 260,[277][278][279][280] Qin et al 277 fabricated an anode containing metallic K infused on an aligned carbon nanotube membrane (ACM); this structure has better cycling performance due to a good wettability to potassium. A strong capillary force obtained from the ACM host offers adequate K nucleation sites for confining the deposited K and smooth charge transfer between electrode and electrolyte during cycling.…”
Section: Carbon Host For Metal-free Anodementioning
confidence: 99%
“…[1][2][3] KIBs show several competitive advantages for future energy storage including highly abundant electrode materials, 4 even distribution of potassium sources across the globe, 5 fast ion diffusion in organic electrolytes, 6 comparable voltage capabilities to LIBs, 7,8 and compatibility with low-weight Al current collectors. 7,9 On the path toward high-voltage and long cycle life KIBs, substantial research efforts are focused on developing improved electrode materials 4,[10][11][12][13][14][15] and optimization of the electrolyte. 8,9,16 While signicant progress has been made, more effort is still needed to maintain KIBs as a competitive alternative to LIBs.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the strategy is scalable and is anticipated to be applied to other MOF-based materials. 77 Additionally, the diverse in situ characteristics in the catalytic course of oxygen evolution reaction (OER), 78,79 HER, [80][81][82] and oxygen reduction reaction (ORR), 75,[83][84][85] as well as other reactions, the excellent performance in terms of electrochemical energy storage, and the application of SCs, 86 sodium-ion batteries (SIBs), [87][88][89][90] lithium-ion batteries (LIBs), [91][92][93][94][95] and other batteries [96][97][98] have been summarized and highlighted, which is expected to be valuable for comprehending the current advances made in MOF-derived phosphides and their utilization in various fields.…”
Section: Introductionmentioning
confidence: 99%